Impact of additional IT investments on firm-level competitiveness - Fejes, Balázs; Stocker, Miklós (Vezetéstudomány / Budapest Management Review, 2024)
Competitiveness and digitalization are important topics for businesses, as in the rapidly changing environment, they determine the ability to survive and thrive. This study examines the impact of information technology (IT) investments on firms’ competitiveness. The study adopts the dynamic capability approach to examine how IT investments enable firms to adapt to digital transformation and generate value. This study employs causal econometrics methods to test the hypothesis that supplementary IT investments enhance the growth, efficiency, and capital accumulation of firms, which are key indicators of ex-ante competitiveness. The hypotheses are tested on a dataset of 65536 Hungarian firms from 1999 to 2014. Empirical evidence was found to support these hypotheses and confirm the positive relationship between IT investments and firm-level growth, efficiency, and capital accumulation. The findings indicate that a small IT investment does not improve efficiency, while an excessive investment is likely to include irrational investments as well.